DAMPAK PENGGUNAAN PAJAK ROKOK DAN INTERCEPT DAU TERHADAP DEFISIT DJS KESEHATAN - Niar Afdhal Luthfi (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2019)
The deficit experienced by Health Social Security Fund (Dana Jaminan Sosial/DJS) Kesehatan encourages the Government to look forward to the alternative policies that are focused on efforts to strengthen DJS Kesehatan revenues and expenditure efficiency. In 2018, the Government implemented policies of the obligation to use the Cigarette Tax and General Allocation Fund (DAU) intercept (for local government who have National Health Security (JKN) arrears to cover the DJS Kesehatan deficit. The purpose of this study is to see the effectiveness of the obligation to use cigarette tax and DAU intercept in reducing the DJS Kesehatan deficit. The method used is a comparative descriptive method with a quantitative approach using secondary data and information from BPJS Kesehatan. From the analysis, we found that the policy of using cigarette tax and DAU intercept is not effective enough in overcoming the DJS Kesehatan deficit. The other impact is the potency to increase the number of Regional Health Security (Jamkesda) participants registered within the regional government and increase the compliance of regional governments in paying JKN contributions.